Characterization of a Silicon Photomultiplier for the Ultra-Fast Astronomy Telescope - Siyang Li; George F. Smoot (SPIE Proceedings (International Society for Optical Engineering), 2019)
“In this study, we characterized the S13360-3050CS Multi-Pixel Photon Counter (MPPC), a silicon photomultiplier (SiPM) manufactured by Hamamatsu Photonics K.K. Measurements were obtained inside a light tight dark box using 365 nm, 400 nm, 525 nm, 660 nm, 720 nm, 810 nm, and 900 nm light-emitting diodes (LED) and the Citiroc 1A front-end evaluation system manufactured by Weeroc. At a 2.95 V over voltage, we measured a dark count rate of 5.07×10⁵ counts per second at 26 °C, a crosstalk probability of 8.7 %, a photon detection efficiency of 36 % at 400 nm, a linear range of 1.8×10⁷ photons per second, and saturation at 5×10⁸ photons per second. The S13360-3050CS MPPC is a candidate detector for the Ultra-Fast Astronomy (UFA) telescope which will characterize the optical sky in the millisecond to nanosecond timescales using two SiPM arrays operated in coincidence mounted on the 0.7 meter Nazarbayev University Transient Telescope at the Assy-Turgen Astrophysical Observatory (NUTTelA-TAO) located near Almaty, Kazakhstan. One objective of the UFA telescope will be to search for optical counterparts to fast radio bursts (FRB) that can be used to identify the origins of FRB and probe the epoch of reionization and baryonic matter in the interstellar and intergalactic mediums.
Keywords: silicon photomultiplier; MPPC; detector characterization; Ultra-Fast Astronomy; UFA telescope; fast transients; type of access: open access